Pregnant women's willingness to participate in a randomized trial comparing induction of labor at 39 weeks versus expectant management: A survey in the Netherlands. (June 2022) - Croll, Dorothée M.R.; Meuleman, Tessa; de Heus, Roel; de Boer, Marjon A.; Verhoeven, Corine J.M.; Bloemenkamp, Kitty W.M.; van Dillen, Jeroen
Abstract: Introduction: A randomized controlled trial (RCT) in the United States, the ARRIVE trial, has indicated that induction of labor (IOL) in low-risk nulliparous women with a gestational age (GA) of 39 weeks compared to expectant management (EM) resulted in a significant lower rate of cesarean deliveries. The Dutch maternity care system is different compared to the United States with, among other factors, an overall significantly lower percentage of caesarean sections (CS). To investigate whether IOL has a favorable outcome in the Dutch maternity care system, a new trial is advised. In this questionnaire-based study we aim to evaluate whether Dutch low-risk pregnant women would be willing to participate in an RCT comparing IOL at 39 weeks to EM. Materials and methods: We conducted an online survey in 2020 in the Netherlands. Respondent recruitment took place both in outpatient clinics at hospitals and midwife practices and via social media. Inclusion criteria were pregnant women with singleton gestation, GA ≤ 39 weeks, age 18 years or older and residency in the Netherlands. Exclusion criteria were multiple gestation, a history of a CS, planned IOL or CS in current pregnancy and GA > 39 weeks. A subgroup was formed of low risk (receiving primary care) nulliparous women with a gestational age between 34 and 39 weeks, comparable with the ARRIVE trial. Results: Three hundred eighty respondents participated. Of all respondents (nulli- and multiparous), 47 (12.4%) would be willing to participate in the hypothetical RCT and 70 (18.4%) might be willing to participate. Amongst the 70 women in the subgroup 11 women (15.7%) would be willing to participate and 17 (24.3%) might be willing to participate. Discussion and conclusion: Calculating sample size in a country with a low CS rate, in relation to 69.2% of women are not willing to participate in an RCT comparing IOL at 39 weeks with EM, would require >18.000 women to be counselled for participation. We believe such a study is a challenge in the Netherlands.